Macular function assessment by multifocal electroretinogram and microperimetry in macular hole and correlation with visual acuity - Dalan, Daleena; Jaishankar, Durgasri; Madhu, Abinaya; Mani, Karthiga; Ratra, Dhanashree (Nepalese Journal of Ophthalmology, 2020)
Background: Functional outcome of macular hole (MH) surgery can be better assessed with multifocal electroretinogram (mfERG) and microperimetry (MP). It might provide better assessment than the Snellen visual acuity alone. Objectives: To evaluate macular function with mfERG and microperimetry, and assess their correlation with visual acuity in MH. Materials and Methods: A prospective study was done in patients with unilateral,idiopathic full thickness MH. Standard surgery with vitrectomy, internal limiting membrane peeling and gas tamponade was done. Snellen and logMAR visual acuity, mfERG, microperimetry and optical coherence tomography were done pre and postoperatively. Results: Twenty six patients with unilateral macular hole and twenty five age matched controls were included. The mean age of patients was 59.92±9.39 years (range: 40 to 74 years). All the holes were closed after surgery (two required second surgery). The mean visual acuity improved from 0.77±0.34 logMAR to 0.43±0.36 (p =0.03). The mfERG amplitudes differed ring wise, but the average amplitude changed from 26.31±8.82 to 20.52±7.11 (p =0.03). The mean retinal sensitivity changed from 12.98±2.59 to 13.42±2.53 (p =0.11). There was significant correlation between visual acuity and mfERG amplitudes and retinal sensitivity. Regression equations to predict visual outcome could be derived. Conclusions: In MH, mfERG and microperimetry show reduced responses, delay in recovery of function. They show a strong correlation with visual acuity. It is possible to predict vision after surgery with the help of mfERG and MP. Improved ability to predict visual outcome can increase the utility of anatomic success predictors.